KAJIAN SEMIOTIKA TIPOLOGI TANDA PADA TEPAK SIRIH DAN BALE DI MEDAN DELI - Tiara Chairunnisa (Melayu Arts and Performance Journal, 2021)
This study aims to determine how the understanding of Tepak Sirih and Bale Melayu is assessed based on the symbolic aspects, the relationship between the representamen and the object, and the interpretant. The method used is a descriptive qualitative method, applying Charles Sanders Peirce's semiotic theory to provide a clear description of the meaning of the typology of signs found in tepak sirih and bale Melayu in Medan Deli District. The study results explain that the presence of tepak sirih and Malay bale is a sensory representation or sign. In relation to representation and object, the company of tepak sirih and bale Melayu refers to a form or container to place something, namely betel and its perencah (tepak) and rice side dishes (malay bale). Based on the interpretation, the understanding of the tepak sirih and the Malay bale is another equivalent sign, namely as a Malay custom or culture.Keywords: Semiotics; Charles Sanders Peirce; betel palm; Malay bale AbstrakPenelitian ini bertujuan untuk mengetahui bagaimana pemahaman terhadap Tepak Sirih dan Bale Melayu dikaji berdasarkan aspek representamen, hubungan representamen dengan objek, dan interpretan. Metode yang digunakan adalah metode kualitatif deskriptif, dengan penerapan teori semiotika Charles Sanders Peirce, untuk memberikan gambaran secara jelas mengenai pemaknaan tipologi tanda yang terdapat pada tepak sirih dan bale Melayu di Kecamatan Medan Deli. Hasil penelitian menjelaskan bahwa kehadiran tepak sirih dan bale Melayu merupakan suatu representamen atau tanda yang bersifat indrawi. Dalam hubungan representamen dengan objek, kehadiran tepak sirih dan bale Melayu mengacu pada suatu bentuk atau wadah untuk menempatkan sesuatu, yaitu sirih dan perencahnya (tepak) serta nasi dan lauk pauk (bale Melayu). Berdasarkan interpretan, pemahaman terhadap tepak sirih dan bale Melayu merupakan tanda lain yang ekuivalen, yaitu sebagai adat istiadat atau budaya Melayu.Kata Kunci: Semiotika; Charles Sanders Peirce; tepak sirih; bale Melayu.